A Study of Yield, its Components, and Some Technological Characteristics of Local and Introduced Varieties of Bread Wheat (Latakia University Journal -Biological Sciences Series, 2013)
Eight varieties of soft wheat T.aestivum L. were used in the study, four of which were local (sham 6, sham 8, sham 10 and bohoth 4) and four introduced varieties obtained from the Scientific Agricultural Research Center (Tugela, Betta, Bezenchukskaya98 and saratovskaya210) and grown during the periods (2011-2012 and 2012-2013) at Qabu Al Awwamiyya near Lattakia City. The following readings were taken for the studied varieties (yield, plant height, spike length, number of spikelets per spike, weight of 1000 grains, protein content proportion of gluten, ash, and moisture content). Data was analyzed statistically using an analysis of variance. The results showed significant differences between the local and introduced varieties on the one hand, and between the varieties themselves on the other hand. Local varieties were better than the introduced varieties with regards to the protein content, moisture content, proportion of gluten, yield, spike length, number of spikelets per spike, and the 1000-grain weight. The introduced varieties however were superior in plant height and ash. The best varieties among local varieties were (Sham 6 and Sham 10), and Betta among the introduced ones.